Formula funding of public services - Peter C. Smith (Routledge, 2007)
The use of formulae has become widespread in recent years across most developed countries. In the UK, a conservative estimate is that annually 150 billion of public service expenditure is distributed using formulae, in services such as health care, local government, social security and higher education. This book offers a comprehensive introduction to the theory and practice underlying the use of such formulae as a basis for funding public services. The philosophy, design and economic consequences of funding formulae have become key policy issues worldwide. However, till now, there has been no text which brings together the economic, statistical and political issues underlying formula funding. This key book fills that gap. Written by a leading international expert on the design of funding formulae, this important book includes empirical evidence from a range of countries and will be a valuable resource for all those involved in this field.
Keywords: 330